2017
DOI: 10.1186/s40795-017-0178-7
|View full text |Cite
|
Sign up to set email alerts
|

A cross sectional analysis of eating habits and weight status of university students in urban Cameroon

Abstract: Background: The changeover from high school to university is characterized by the inability to make informed food choices and unhealthy eating habits. This study sets out to determine the prevalence of overweight/obesity, examine variations in dietary habits and assess the relationships between some dietary factors and overweight/ obesity in university students. Methods: University students (N = 906, mean age 21.4 ± 2.1 years) that included 434 males and 472 females were recruited using a simple random samplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
21
5
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 38 publications
10
21
5
1
Order By: Relevance
“…7,10,11,15,16 While some studies had a larger sample size(>1000); few other studies had a smaller sample size than present study(<200). 8,9,[12][13][14]17,18 Female students were more in number compared to males, which is similar to most other studies. [10][11][12][13][14][15][16][17][18] But some studies had more male students than females.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…7,10,11,15,16 While some studies had a larger sample size(>1000); few other studies had a smaller sample size than present study(<200). 8,9,[12][13][14]17,18 Female students were more in number compared to males, which is similar to most other studies. [10][11][12][13][14][15][16][17][18] But some studies had more male students than females.…”
Section: Discussionsupporting
confidence: 80%
“…8,9,[12][13][14]17,18 Female students were more in number compared to males, which is similar to most other studies. [10][11][12][13][14][15][16][17][18] But some studies had more male students than females. [7][8][9] While another study conducted in Saudi Arabia had only male students as study subjects.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…A study from the United States reported that frequent RTE food consumption led to increased energy intake, resulting in overweight and obesity [36]. This finding is in line with studies from Cameroon, Luxembourg, and Indonesia [37][38][39].…”
Section: Discussionsupporting
confidence: 75%